Antioxidants in sport nutrition [ - Lamprecht, Manfred (CRC Press, 2015)
"Antioxidant use in sports is controversial due to existing evidence that it both supports and hurts athletic performance. This book presents information on antioxidants, specifically for athletes, and their roles in sports nutrition. It stresses how antioxidants affect exercise performance, health, and immunity. Chapters cover oxidative stress; basic nutrition for athletes; major dietary antioxidants; sports supplements; performance/adaptation to exercise; antioxidants role in health and immunity; reviews on vitamins C, E, beta carotene, and minerals in sports nutrition; and roles polyphenols play in high-performance sport" -- Provided by publisher